The Impact Machine Learning Algorithms : Study Meta-Analysis - Sani, Asrul; Oktavio, Adrie; Metasari, Rean; Santosa, Tomi Apra; sjoraida, Diah Fatma; Rembe, Elismayanti; Amri, Miftachul; Guna, Bucky Wibawa Karya (INTECOMS: Journal of Information Technology and Computer Science, 2024)
Machine Learning (ML) algorithms have revolutionized various fields, including science, technology, and business. This study conducted a meta-analysis to review the impact of ML algorithms on various domains. This research is a type of meta-analysis research. The data sources in this study come from 12 national and international journals published in 2022-2024. Data collection techniques through direct observation through journal databases. The inclusion criteria in this meta-analysis are research obtained from google scholar; ScienceDirect and ERIC, Research must be related to machine learning algorithms, research has complete data to calculate the effect size value. Data analysis in this study was conducted by statistical analysis with JSAP 0.16.3 application. The results of the study concluded that ML lgoritma has a significant impact on various fields including the discovery of new knowledge, process efficiency and accuracy in prediction with an effect size value of 0.793; p < 0.001. These findings show that ML algorithms have great potential to improve performance and efficiency in various fields.